ANALISA PENGARUH JUMLAH TENAGA KERJA, NILAI EKSPOR DAN NILAI INVESTASI PADA INDUSTRI PENGOLAHAN TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN LUMAJANG - Kurniawati, Vina; Pudjihardjo, M.; Sakti, Rachmad Kresna (EP FEB UNS, 2018)
The processing industry has become one of the supporters of the regional economy. This is shown from several studies and studies which states that the processing industry is the second largest passenger of GRDP after the primary sector. This study aims to influence the amount of labor, export value and investment value of wood processing industry and food processing industry in Lumajang regency with observation period from 2002 until 2016. This research model uses quantitative descriptive analysis with panel data regression research method. The estimation model used is fixed effect model for both processing industries. Sample data obtained by using purposive sampling method, where data retrieval is based on certain criteria.The result of research with t test shows that the amount of labor, export value and investment value in wood processing industry have positive and significant influence to economic growth. For the food processing industry, the amount of labor is negative and does not affect the economic growth, while the value of exports and investment value have a positive and significant impact on economic growth. Could be this is because the investment in food processing industry is intended to increase capital goods or equipment, thus affecting the reduction in the number of labor. Through the test f, all independent variables in the two processing industries simultaneously together influence the dependent variable. Keywords: Economic Growth, Processing Industry, Labor, Export, InvestmentJEL Classification: O1, O47